Age-associated microglial transcriptome leads to diminished immunogenicity and dysregulation of MCT4 and P2RY12/P2RY13 related functions - Martin Škandík; Lara Friess; Guillermo Vázquez-Cabrera; Lily Keane; Kathleen Grabert; Mireia Cruz De los Santos; Mercedes Posada-Pérez; Austeja Baleviciute; Mathilde Cheray; Bertrand Joseph (Cell Death Discovery)
Abstract The aging process is marked by a time-dependent deterioration in cellular functions, particularly the immune and neural systems. Understanding the phenotype acquisition of microglia, the sentinel immune cells of the brain, is crucial for understanding the nature of age-related neurological diseases. However, the specific phenotype adopted by microglia during aging remains a subject of debate and is contingent on the chosen experimental model. To address these unresolved questions, we employed a novel and highly controlled approach utilizing long-term cultivated BV-2 microglia, exempted from additional external stimuli. Our findings revealed that aged microglial cells, in comparison to their younger counterparts, acquire a distinct gene expression profile, primarily characterized by alterations in microglial immune response. Indeed, pro-inflammatory stimulated aged and young BV-2 microglia exhibited similar transcriptomic profiles, yet the response intensity to the stimulus was markedly muted in the aged microglia. Functional neurotoxic assays confirmed diminished neuronal death in coculture with aged, activated microglia, underscoring a compromised immune response. Furthermore, a subsequent comparative analysis of aged BV-2 microglia with established transcriptomic microglial datasets from aged mice and humans identified 13 overlapping genes, laying the foundation for identifying core microglial aging signature. Particularly noteworthy were SLC16A3 and P2RY13, which consistently exhibited upregulation and downregulation, respectively, across all datasets. Additionally, four other genes—CAPG, LGALS3BP, NRIP1, and P2RY12—were found to share regulatory patterns in response to both aging and extrinsic activation. An in-depth investigation focused on SLC16A3, encoding the high-affinity lactate transporter MCT4, revealed disruptions in extracellular acidification rate and lactate concentration with age. Microglial purine sensing and motility capacities, regulated by P2RY12/P2RY13, displayed age-related alterations. Remarkably, protein analysis in human brain tissue validated the observed upregulation of MCT4 and downregulation of P2RY12 in aged microglia. In conclusion, our study unveils a distinct phenotype in aged microglia characterized by compromised immune responsiveness. Through the integration of in vitro cultured BV-2 microglia with primary microglia datasets, we identify critical molecular determinants of microglial cellular aging confirmed in human-aged brain tissue. This comprehensive approach offers potential insights for understanding and potentially reprogramming aged microglia, with implications for combating age-related neurological disorders.